Agricultural drought monitoring using modified TVDI and dynamic drought thresholds in the upper and middle Huai River Basin, China - Dui Huang; Tao Ma; Jiufu Liu; Jianyun Zhang (Journal of Hydrology: Regional Studies)
Study Region: The upper and middle reaches of the Huai River Basin. Study Focus: The study seeks to enhance the monitoring of agricultural drought by introducing a modified temperature vegetation drought index (TVDIm) and developing a flexible drought threshold that considers crop growth stages and water requirements. This approach intends to accurately identify areas impacted by drought. The TVDIm enhances the detection of wet and dry boundaries in the regions of land surface temperature (LST)—normalized difference vegetation index (NDVI)—and LST—enhanced vegetation index (EVI). The TVDIm derived using the NDVI and EVI indices are denoted as TVDINDVIm and TVDIEVIm, respectively. New Hydrological Insights: The findings indicate that TVDIm, particularly TVDIEVIm, has a stronger association with soil moisture at different depths in comparison to conventional TVDI. The annual comparisons demonstrate that the TVDIm index is associated with soil moisture throughout several soil layers, accommodating the diverse water needs of different phases of crop growth. Using the strong correlation between TVDIEVIm and observed data, we developed dynamic drought thresholds (ranging from 0.8 to 0.85) that are tailored to different crop growth stages. These thresholds greatly reduce the spatial extent of areas classified as experiencing drought, decreasing by 15,500–79,700 square kilometres compared to the threshold of 0.67. Additionally, they increase the intra-annual variability of areas affected by drought.